Perkembangan Populasi Liriomyza brassicae Riley (Diptera: Agromyzidae) dan Struktur Komunitas Parasitoid yang Berasosiasi dengan Tanaman Kubis-kubisan (Brassicaceae) di Provinsi Bali - WAYAN SUDIANTARA PUTRA; I WAYAN SUPARTHA; DWI WIDANINGSIH (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2018)
Populations Development of Liriomyza brassicae Riley (Diptera: Agromyzidae) and Community Structure of Parasitoid Associated with Cabbage (Brassicaceae) in Bali The research to find the morphological characteristics of Liriomyza brassicae, density and population development of L. brassicae, the community structure of parasitoid associated with cabbage (Brassicaceae) in Bali. This research was conducted in Baturiti Village (<850 m asl) Tabanan Regency, Kintamani Village (850-1000 m asl) Bangli Regency and Kembang Merta Village (> 1000 m asl) Tabanan Regency. The research was carried out from January 2018 to March 2018. The sampling method was carried out purposively and the number of samples taken from 20-50 leaves were attacked by Liriomyza. Identification of Liriomyza and parasitoid was carried out at the Integrated Pest and Disease Control Laboratory (IPM Lab) Faculty of Agriculture, Udayana University. The results showed that the morphological characteristics of L. brassicae namely mesonotum were black with yellow on the side, the scutellum was yellow with both brown corners colored, coxa and femur brownish yellow, yellow mesopleura, and the dorsal abdomen had a longitudinal line that cut the segment first abdomen to second abdomen. The result showed that population density of L. brassicae highest in broccoli at (> 1000 m asl) and the lowest in green mustard at (<850 m asl). The result showed that population development of L. brassicae highest at plant age 5 MST and population decline occurred at the plant age of 9 MST. The results also showed that there were 2 species of parasitoids associated with L. brassicae namely Opius sp., and Hemiptarsernus varicornis. The diversity index, abundance index, and parasitoid domination index associated with L.brassicae were highest in broccoli at (> 1000 m asl) and lowest in mustard at (<850 m asl).